O‘ZBEKISTONDA “UNUTILISH HUQUQI”NI TA’MINLASHNING HUQUQIY MEXANIZMLARINI YANADA TAKOMILLASHTIRISH - Saparbayeva Maftuna Ikrom qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
This article scientifically analyzes the issue of improving legal mechanisms for ensuring the “right to be forgotten” in the Republic of Uzbekistan -  namely, the individual’s right to request the deletion, de-indexing, or restriction of the processing of outdated, inaccurate, or no longer relevant personal data. In the context of long-term storage and free dissemination of digital information, the balance between the inviolability of privacy and freedom of information is becoming an important theoretical and practical challenge for the national legal system. The study is based on a comparative-functional assessment of the existing regulatory framework, international standards, and law enforcement practice. Methodology: normative-legal analysis, comparative legal approach, doctrinal interpretation, and functional modeling of law enforcement practice. The scientific novelty lies in conceptualizing the “right to be forgotten” as an independent subjective right, defining its scope within a three-layer mechanism — deletion, de-indexing, and restriction -  developing a model of differentiated obligations, and proposing a step-by-step dispute resolution procedure.